Towards ultrafast dynamics with split-pulse X-ray photon correlation spectroscopy at free electron laser sources - W. Roseker (Nature Portfolio, 2018)
X-ray photon correlation spectroscopy has been mainly used to measure slow dynamics using synchrotron sources. Here the authors demonstrate the split-and- delay pulse set-up to study nanosecond dynamics of gold nanoparticles using XPCS with free electron laser pulses.